A cooperação internacional como instrumento jurídico de prevenção e combate à corrupção - Nunes, Antonio Carlos Ozório (2008)
The study analyses the importance of international cooperation as a legal instrument in the prevention and fight against corruption. Starting from the research into international relations through a cooperate view, we built an approach regarding the contemporary international order, whose actors cohabit under conditions of interdependency, in a scenario that demands bigger institutionalization and cooperation ties, namely in the restrain of complex and global topics, such as the subject of corruption. Corruption is one of the main topics in the international agenda and because it causes such unwanted effects to the economy and to the economic and social development of countries, especially the developing ones, the fight against it has gained in the last years, deserved prominence in the international circuit, with no less than six International Conventions about the subject, highlighting the United Nations Convention against Corruption, in 2003, which is the most comprehensive legally binding document, demanding efforts and mechanisms from the Estates in the fight against the phenomenon. The study looks at the need for a global effort to prevent and fight corruption, especially through international cooperation, focusing on two cooperative outlooks which can be effective mechanisms in the fight against the problem: the international technical cooperation, through which the Estates will be able to collaborate among each other in the acquisition, transfer and dissemination of technical knowledge for the qualification of its human resources and the strengthening of its institutions; and the international legal cooperation, destined to the combined facing of the problem by the Estates, which will strive in the efforts to punish the ones responsible, in the fight against money laundering and to recover the assets diverted to other countries, due to the practice of corruption, concluding that international cooperation has ceased being a courtesy among the Estates to become a necessity and an obligation in present days